Study of c-s-h formation of cemented sediment brick - Ean L.W.; Malek M.A.; Mohammed B.S.; Tang C.-W.; Ng C.Y. (Springer Science and Business Media Deutschland GmbH, 2023)
Amorphous materials; Brick; Calcite; Calcium silicate; Cements; Energy dispersive spectroscopy; Hydration; Offshore oil well production; Scanning electron microscopy; Silica; Silicon; Cement content; Dense materials; Energy dispersive spectroscopies (EDS); Hydration products; Morphological structures; Morphology analysis; Sediment content; Structure formations; Sediments